Chronicles and the priestly literature of the Hebrew Bible - Jeon, Jaeyoung; Jonker, Louis C. (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2021)
Frontmatter -- Preface -- Table of Contents -- Abbreviations -- Introduction -- Part 1 Consonance and Dissonance -- The Book of Chronicles through the Ages: A Cinderella or a Sleeping Beauty? -- I Consonance, Continuity, and Mutual Influence -- Theocratic Reworking in the Pentateuch -- Numbers and Chronicles: Close Relatives 2 -- נפשׁשׁ אדם and the Associations of 1 Chronicles 5 in the Hebrew Bible -- II Dissonance, Discontinuity, and Alteration -- The High Priest in Chronicles and in the Priestly Traditions of the Pentateuch -- The Tribes of Israel in Ezekiel and Chronicles -- Sacrifices in Chronicles: How Priestly Are They? -- Part 2 Interpreting the Consonance and Dissonance -- III Inclusive Reception and Creative Interpretation -- Scribes in the Post-Exilic Temple: A Social Perspective -- Atonement, Sacred Space and Ritual Time: The Chronicler as Reader of Priestly Pentateuchal Narrative -- Grundgeschichte und Chronik – Kontinuität und Diskontinuität in Altisraels Geschichtsschreibung -- Conversational Implicatures in the Book of Chronicles -- Levites of Memory in Chronicles and Some Considerations about Historical Levites in Late-Persian Yehud -- IV Ideological Conflicts and Scribal Debates -- Genealogies as Tools: The Case of P and Chronicles -- David in the role of a second Moses – The revelation of the temple-model (tabnît) in 1 Chronicles 28 -- The righteousness of the Levites in Chronicles and Ezekiel -- The Levites and Idolatry: A Scribal Debate in Ezekiel 44 and Chronicles -- V Ezra-Nehemiah: Between P and Chronicles -- The Role of Priests and Levites in the Composition of Ezra-Nehemiah: Some Points for Consideration -- Levites, Holiness and Late Achaemenid / Early Hellenistic Literature Formation: Where does Ezra-Nehemiah fit into the Discourse? -- Index of Sources -- Index of Modern Authors -- Subject Index